HUBUNGAN PENGETAHUAN DAN SIKAP KADER POSYANDU MENGENAI PENYELENGGARAAN PEMBERIAN MAKANAN TAMBAHAN (PMT) LOKAL BALITA DI WILAYAH KERJA PUSKESMAS NGAMPEL KABUPATEN KENDAL - Surani, Endang; Rosyidah, Hanifatur; Salsabila, Dian (Jurnal Kesehatan Manarang, 2025)
Toddler nutrition plays a crucial role in growth and development, yet problems such as stunting, wasting, underweight, and obesity remain prevalent in Indonesia. Although the stunting rate decreased to 21.6% in 2022, this figure remains above the WHO target of <20%. In Central Java, wasting and underweight rates have increased, and Kendal Regency reported 598 malnutrition cases in 2023. In the Ngampel Health Center area, 69 toddlers were wasted, 176 were underweight, and 95 were stunted. This study aimed to analyze the relationship between the knowledge and attitudes of posyandu cadres regarding the implementation of local supplementary feeding (PMT) for toddlers. This quantitative study employed a cross-sectional design. The population consisted of 260 posyandu cadres, and a purposive sample of 51 cadres was selected. Data were collected in May 2024 using a validated questionnaire assessing knowledge (Guttman scale) and attitudes (Likert scale). Data were analyzed using the Spearman’s rank correlation test. The results showed no significant relationship between knowledge and attitudes (r = 0.058, p = 0.685), indicating a very weak and statistically non-significant association. The lack of association suggests that cadre attitudes may not be determined solely by knowledge but also by other factors such as experience, motivation, training opportunities, and institutional support. These findings highlight the importance of strengthening cadre capacity not only through knowledge transfer but also through practical skill development and supportive supervision to encourage positive attitudes toward local PMT implementation.